Degradation method of polyurethane acrylic resin material and degradable polyurethane acrylic resin material
By using the degradation solution containing reactivity NH or NH2 groups and OH groups to heat the polyurethane acrylic resin material, it solves the problem of difficulty recycling composite materials, realizes high -efficiency degradation and recycling, reduces energy consumption and cost, and reduces it. Environmental pollution.
Patent Information
- Application Number
- CN202411718276.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-30
- Filing Date
- 2023-01-06
- Publication Date
- 2025-01-28
AI Technical Summary
Due to its three-dimensional mesh crosslinking state, polyurethane acrylic resin composites are difficult to recover by melting or dissolving. The existing recycling methods are energy-consuming, costly and have serious environmental pollution.
The degradation solution containing reactivity NH or NH2 groups and OH groups is used to heat the polyurethane acrylic resin material, achieve efficient degradation through ammonia and alcoholic solution, and separate degradation liquid through decompression distillation.
The efficient degradation and recycling of polyurethane acrylic resin materials reduces energy consumption and cost, and reduces environmental pollution, and promotes sustainable recycling of composite materials.
Smart Images

Figure CN119371716A_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of January 6, 2023, an application number of 202310017965.0, and an invention name of "Degradation method of polyurethane acrylic resin material, polyurethane acrylic resin, its composition, preparation method and composite material". Technical Field
[0002] The present invention relates to a degradation method of polyurethane acrylic resin material, in particular to a degradation method of polyurethane acrylic resin material containing network cross-linking, polyurethane acrylic resin, its composition, preparation method and composite material. Background Art
[0003] Polyurethane acrylic resin has a wide design space and can be adjusted to be rigid or flexible according to needs. The advantages of its molecular structure include good corrosion resistance, good wear resistance, good adhesion, good heat resistance, good mechanical properties, good wetting properties for a variety of fibers, etc., which are suitable for composite material structure design. However, due to the above excellent properties, it is difficult to decompose and recycle this type of composite material, which will eventually cause problems such as lack of landfill sites and environmental pollution. Therefore, the decomposition and recycling of waste composite materials has become an important issue.
[0004] Since the polyurethane acrylic resin composite material is in a three-dimensional network cross-linked state, it is difficult to recycle it by melting or dissolving. According to the existing technology, the polyurethane acrylic resin composite material can only be recycled by means of huge energy or time consumption and high cost, such as landfill and incineration, and lacks degradation recycling technology. However, these two treatment methods of landfill and incineration are gradually becoming unfeasible in the future. Only by developing in the direction of resin degradation can the composite material be recycled to achieve the purpose of waste reduction.
[0005] In view of this, how to find appropriate degradation liquid to degrade polyurethane acrylic resin and then achieve the purpose of recycling has become the goal of relevant industries. Summary of the invention
[0006] One object of the present invention is to provide a method for degrading a polyurethane acrylic resin material, which comprises using a polyurethane acrylic resin material containing reactive NH or NH 2 The degradation liquid of the groups and OH groups is heated to decompose the polyurethane acrylic resin material to achieve the purpose of recycling and reuse.
[0007] Another object of the present invention is to provide a polyurethane acrylic resin, its composition, preparation method and composite material, which is synthesized by subjecting isocyanate and polyol to polyurethane acrylate reaction and adding diluent monomer to synthesize degradable polyurethane acrylic resin.
[0008] One embodiment of the present invention provides a method for degrading a polyurethane acrylic resin material, which comprises providing a polyurethane acrylic resin material and performing a degradation step. The polyurethane acrylic resin material has a carbon-carbon double bond. The degradation step is to degrade the polyurethane acrylic resin material into degradation products using a degradation compound, wherein the degradation products include alcohols or amines.
[0009] According to the method for degrading the polyurethane acrylic resin material as described in the preceding paragraph, the degradation product may include polyols.
[0010] According to the method for degrading the polyurethane acrylic resin material described in the previous paragraph, the polyurethane acrylic resin material may include polyurethane acrylic resin and fibers.
[0011] According to the degradation method of the polyurethane acrylic resin material described in the preceding paragraph, the degradation compound may have a structure as shown in formula (i):
[0012]
[0013] Wherein, X may be an alkyl group or an oxyalkyl group, m may be 1 or 2 and m+n=3.
[0014] According to the degradation method of the polyurethane acrylic resin material described in the preceding paragraph, the degradation products may include aromatic amines.
[0015] According to the method for degrading polyurethane acrylic resin material described in the preceding paragraph, the degradation compound may include reactive NH groups, reactive NH 2 Groups or reactive OH groups.
[0016] According to the degradation method of the polyurethane acrylic resin material described in the previous paragraph, the polyurethane acrylic resin material can be obtained by curing the polyurethane acrylic resin, the polyurethane acrylic resin can contain polyurethane acrylic resin oligomers, and the weight proportion of the polyurethane acrylic resin oligomers can be more than 40% of the total weight of the polyurethane acrylic resin.
[0017] According to the degradation method of the polyurethane acrylic resin material described in the preceding paragraph, the polyurethane acrylic resin oligomer may have a structure as shown in formula (I):
[0018]
[0019] Wherein, A can be polyethoxy, polypropoxy or polytetrahydrofuranyl.
[0020] Another embodiment of the present invention provides a degradable polyurethane acrylic resin material, which comprises polyurethane acrylic resin and fiber. The polyurethane acrylic resin has carbon-carbon double bonds. The fiber is glass fiber, carbon fiber, polyamide fiber or a mixture thereof.
[0021] Another embodiment of the present invention provides a degradable polyurethane acrylic resin material that can be used as a surface coating, which comprises polyurethane acrylic resin and titanium dioxide, silicon dioxide, calcium carbonate, aluminum oxide, aluminum hydroxide, silicon carbide or a combination thereof. The polyurethane acrylic resin has a carbon-carbon double bond.
[0022] Thus, the degradation method of the polyurethane acrylic resin material of the present invention mainly uses a reactive NH or NH 2 The degradation liquid of the hydroxyl radical and the OH radical is heated to degrade the polyurethane acrylic resin material, and the degradation liquid can be separated by reduced pressure distillation to make it reusable. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to make the above and other objects, features, advantages and embodiments of the present invention more clearly understood, the following are the descriptions of the accompanying drawings:
[0024] Figure 1 FIG. 4 is a flowchart showing a method for degrading a polyurethane acrylic resin material according to an embodiment of the present invention.
[0025] Figure 2 FIG. 4 is a flow chart showing the steps of a method for preparing polyurethane acrylic resin according to another embodiment of the present invention.
[0026] Figure 3 FIG. 4 is a flow chart showing a method for preparing polyurethane acrylic resin according to another embodiment of the present invention.
[0027]
Main component symbol description
[0028] 100: Degradation method of polyurethane acrylic resin material
[0029] 200,300: Preparation method of polyurethane acrylic resin
[0030] 110,120,130,140,210,220,310,320,330: Steps DETAILED DESCRIPTION
[0031] The following will discuss various embodiments of the present invention in more detail. However, this embodiment can be an application of various inventive concepts and can be specifically implemented in various specific scopes. The specific embodiments are for illustration purposes only and are not limited to the scope of the disclosure.
[0032] <Degradation Method of Polyurethane Acrylic Resin Material>
[0033] See also Figure 1 , which is a flow chart showing the steps of a method 100 for degrading a polyurethane acrylic resin material according to one embodiment of the present invention. Figure 1In the embodiment, the method 100 for degrading a polyurethane acrylic resin material includes steps 110 , 120 , 130 and 140 .
[0034] Step 110 is to provide a polyurethane acrylic resin material, which is obtained by curing a polyurethane acrylic resin. Specifically, the polyurethane acrylic resin material of the present invention can be a polyurethane acrylic resin cured product or a composite material containing a polyurethane acrylic resin cured product, wherein the polyurethane acrylic resin cured product can be cured at room temperature or high temperature by adding a conventional accelerator and a free radical initiator to form a network cross-linked cured product, and the composite material containing the polyurethane acrylic resin cured product is obtained by impregnating a polyurethane acrylic resin and a fiber at room temperature or high temperature, and the fiber can be glass fiber, carbon fiber, polyamide fiber or a mixture thereof, but is not limited thereto.
[0035] Step 120 is to provide a degradation solution, which at least contains a degradation compound, and the degradation compound at least contains reactive NH or NH 2 Groups and reactive OH groups. Specifically, reactive NH or NH 2 The group and the reactive OH group are functional groups that can react with the polyurethane acrylic resin, and can be subjected to aminolysis and alcoholysis without damaging the fibers in the composite material. Specifically, the degradation compound can have a structure as shown in formula (i):
[0036]
[0037] Wherein, X is an alkyl group or an oxyalkyl group, m is 1 or 2 and m+n=3, which can still have sufficient reactivity to the polyurethane acrylic resin without adding a catalyst, thereby achieving the purpose of high-efficiency degradation.
[0038] Step 130 is a mixing step, which is to mix the polyurethane acrylic resin material with the degradation liquid to form a degradation mixture.
[0039] Step 140 is a heating step, which is to heat the degradation mixture to a degradation temperature and maintain the degradation time to degrade the polyurethane acrylic resin material, wherein the degradation temperature can be 135° C. to the boiling point of the degradation liquid, and the degradation time can be 2 hours to 24 hours.
[0040] Thus, the present invention uses aminolysis and alcoholysis to make the polyurethane acrylic resin material containing network crosslinks and at least containing reactive NH or NH 2The degradation liquid reacts with the reactive OH groups and achieves a highly efficient degradation effect by increasing the temperature. The highest degradation temperature can be implemented at the boiling point of the degradation liquid. The excess degradation liquid can act as a solvent during the degradation process to dilute and suspend the fiber. After the degradation is completed, the volatile substances can be separated by vacuum distillation. The volatile substances are the reactive NH or NH 2 In addition, after the composite material containing the polyurethane acrylic resin solid is degraded, the polyurethane acrylic resin can be decomposed and removed to form recycled fibers without plastic attachment, which can realize the recycling mechanism of separating fibers and organic substances.
[0041] According to the method 100 for degrading a polyurethane acrylic resin material of the present invention, more than 40% of the total weight of the polyurethane acrylic resin is an oligomer, and the oligomer has a structure as shown in formula (I):
[0042]
[0043] Wherein, A is polyethoxy, polypropoxy or polytetrahydrofuranyl.
[0044] According to the polyurethane acrylic resin material degradation method 100 of the present invention, the preparation of the polyurethane acrylic resin can refer to Figure 2 The description is as follows, Figure 2 A flowchart of a method 200 for preparing polyurethane acrylic resin according to another embodiment of the present invention is shown. Figure 2 In the present invention, the preparation method 200 of polyurethane acrylic resin includes step 210 and step 220.
[0045] Step 210 is a polyurethane polymerization step, which is to mix the isocyanate compound, the inhibitor and the catalyst in the diluted monomer, and heat it to a first temperature to obtain a first mixture, and then add the polyol compound to the first mixture and maintain the reaction at the first temperature to obtain a second mixture.
[0046] Step 220 is a polyurethane acrylate step, which is to add a hydroxyl-containing (meth)acrylate compound into the second mixture and maintain the reaction at the first temperature to obtain a polyurethane acrylate resin.
[0047] The aforementioned isocyanate compound may be a difunctional or multifunctional isocyanate compound, wherein the difunctional or multifunctional isocyanate compound may be an aromatic ring isocyanate, and the aromatic ring isocyanate may be tolyl diisocyanate, polymethylene phenyl isocyanate, diphenylmethane diisocyanate or a mixture thereof. Specifically, the aforementioned isocyanate compound may be, but is not limited to, one or more of MR200 (purchased from Tosoh), PM200 (purchased from Wanhua), M20S (purchased from BASF), 44V20 (purchased from Costron), 5005 (purchased from Huntsman), NM (purchased from Tosoh), and MDI-50 (purchased from Wanhua).
[0048] The aforementioned inhibitor is a conventional inhibitor added to a general free radical curing system resin to ensure the storage property (stability) of the resin. A suitable inhibitor can be selected from the conventional inhibitors according to the needs and will not be described in detail here.
[0049] The catalyst may be organic tin, organic bismuth or organic zinc, and the added amount of the catalyst may be 50 ppm to 200 ppm of the total content of the polyurethane acrylic resin.
[0050] The aforementioned diluent monomer is a free radical-curable diluent monomer, which may be methyl (meth)acrylate, ethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexane (meth)acrylate, tetrahydrofuran (meth)acrylate, styrene, methylstyrene, vinyltoluene or a mixture thereof, and the first temperature may be 40°C to 80°C, preferably 50°C to 70°C.
[0051] The aforementioned polyol compound may be a difunctional or multifunctional polyol compound, which may be polyoxyethylene ether, polyoxypropylene ether, polytetrahydrofuran or a mixture thereof, and the number average molecular weight of the polyol compound is less than 2000. If the number average molecular weight of the polyol compound is greater than 2000, it is difficult to achieve the demand for high rigidity composite materials.
[0052] The hydroxyl-containing (meth)acrylate compound may be hydroxyethyl methacrylate (2-HEMA), hydroxyethyl acrylate (2-HEA), hydroxypropyl methacrylate (2-HPMA), hydroxypropyl acrylate (2-HPA) or a mixture thereof.
[0053] The equivalent ratio of the NCO group of the aforementioned isocyanate compound to the OH group of the polyol compound can be 1.5:1 to 10:1. When the ratio of NCO group / OH group is lower than 1.5, the polymerization molecular weight will be too high and the rigidity will be insufficient. When the ratio of NCO group / OH group is higher than 10, the rigidity after curing will be too high and the degradation efficiency will be poor. In addition, the NCO group of the isocyanate compound will remain in step 210, so that the hydroxyl-containing (meth)acrylate compound in step 220 can react with it, so the equivalent ratio of the OH group of the hydroxyl-containing (meth)acrylate compound to the NCO group of the isocyanate compound remaining after the reaction can be 1:1 to 1.05:1.
[0054] The polyurethane acrylic resin comprises an oligomer as shown in formula (I), and the oligomer is described above and will not be described here. Specifically, the composition of the polyurethane acrylic resin comprises an isocyanate compound, a polyol compound, a hydroxyl-containing (meth)acrylate compound and a diluent monomer, and the oligomer is synthesized from the isocyanate compound, the polyol compound and the hydroxyl-containing (meth)acrylate compound.
[0055] According to the polyurethane acrylic resin material degradation method 100 of the present invention, the preparation of the polyurethane acrylic resin can also refer to Figure 3 The description is as follows, Figure 3 A flowchart of a method 300 for preparing polyurethane acrylic resin according to another embodiment of the present invention is shown. Figure 3 In the present invention, the preparation method 300 of polyurethane acrylic resin includes step 310, step 320 and step 330.
[0056] For details of step 310 and step 320, please refer to the above steps 210 and 220, which will not be described in detail here. In detail, step 330 is a dilution step, which is to react the second mixture containing hydroxyl (methyl) acrylate compound at the first temperature (i.e., the third mixture), cool down and add dilution monomer to obtain polyurethane acrylic resin. Specifically, step 330 involves the adjustment of the operating viscosity, wherein the viscosity of the vacuum infusion resin is preferably 100cps to 250cps, and the viscosity of the hand-layup resin is preferably 300cps to 450cps. By adding an appropriate amount of dilution monomer in step 330 to control the viscosity of the polyurethane acrylic resin, a polyurethane acrylic resin more suitable for operation is obtained, so as to facilitate the subsequent application of the polyurethane acrylic resin material. The aforementioned application refers to the use of hand lay-up molding, compression molding, prepreg molding, pultrusion molding, fiber winding, resin transfer molding, and vacuum infusion molding to manufacture the corresponding products. For the dilution monomer, please refer to the above description, which will not be described in detail here.
[0057] In addition, the dilution step in the preparation method 300 of the polyurethane acrylic resin of the present invention is determined by the viscosity requirement of the operation process, and in the preparation method 200 of the polyurethane acrylic resin of the present invention, the polyurethane acrylic resin of the present invention can be obtained after the polyurethane acrylate esterification step.
[0058] The polyurethane acrylic resin of the present invention utilizes difunctional or higher isocyanate and polyol to carry out polyurethane chain extension reaction, and then is capped with a hydroxyl-containing acrylate compound, and then is diluted with a free radical curable diluent monomer according to the operating viscosity to obtain a degradable polyurethane acrylic resin.
[0059] In detail, the reaction schematic equation of the preparation method of the polyurethane acrylic resin of the present invention is shown in Table 1 below, wherein M is a diluent monomer, which forms a network copolymer structure with the polyurethane acrylic resin after free radical curing.
[0060]
[0061] In addition, the degradation reaction equation of polyurethane acrylic resin is shown in Table 2 below, wherein the polyurethane acrylic resin structure forms small molecular carbamate, small molecular urea ester, polyol and polyacrylic acid molecules through alcoholysis and aminolysis. Under continuous action, the final degradation products are speculated to be aromatic amine compounds, oxazolidinone, carbamate alcohol amine and urea diol.
[0062]
[0063]
[0064] In other embodiments, more than 40% of the total weight of the polyurethane acrylic resin in the degradation method of the polyurethane acrylic resin material of the present invention is an oligomer prepared from the composition for preparing the polyurethane acrylic resin of the present invention, and the oligomer has a structure as shown in formula (I) of the present invention, but is not limited thereto.
[0065] The polyurethane acrylic resin material of the present invention can be applied as surface coating, adhesive, 3D printing or main structure layer, and can be added with fillers such as titanium dioxide, silicon dioxide, calcium carbonate, aluminum oxide, aluminum hydroxide, silicon carbide or a combination thereof according to its function, so as to be applied to the manufacture of automobile parts, marine parts, rail car parts, sports product parts, aviation parts, wind turbine parts, furniture parts, and building parts.
[0066] The present invention is further illustrated by the following specific embodiments, which are used to facilitate those skilled in the art to which the present invention belongs, so that they can fully utilize and practice the present invention without excessive interpretation. These embodiments should not be regarded as limiting the scope of the present invention, but are used to illustrate how to implement the materials and methods of the present invention.
[0067] <Synthesis example>
[0068] <Synthesis of polyurethane acrylic resin>
[0069] Synthesis Example 1: 280 g of polymethylene phenyl isocyanate, 0.318 g of 2,5-dihydroxytoluene and 0.159 g of catalyst (DBTDL) are dispersed in 228 g of methyl methacrylate, mixed evenly in a reactor and heated to 45°C to 60°C for standby use. Next, 138.9 g of polypropylene glycol (PPG400) is slowly added dropwise to the reactor for 40 to 60 minutes, the temperature is controlled below 60°C during the addition, and the temperature is maintained at 45°C to 60°C for 2 to 4 hours after the addition is completed. After that, 180.8 g of hydroxyethyl methacrylate (2-HEMA) is slowly added dropwise for 40 to 60 minutes, the temperature is controlled below 60°C during the addition, and the temperature is maintained at 45°C to 60°C for 2 to 4 hours after the addition is completed. When the NCO value is lower than 0.5%, 228 g of methyl methacrylate is added for dilution to obtain the polyurethane acrylic resin of Synthesis Example 1, which has a viscosity of 130 cps.
[0070] Synthesis Example 2: 250 g of polymethylene phenyl isocyanate, 0.317 g of 2,5-dihydroxytoluene and 0.159 g of catalyst (DBTDL) are dispersed in 227 g of methyl methacrylate, mixed evenly in a reactor and heated to 45°C to 60°C for standby use. Next, 186 g of polyethylene glycol (PEG600) is slowly added dropwise to the above reactor, the addition time is 40 to 60 minutes, the temperature is controlled below 60°C during the addition, the addition is completed at 45°C to 60°C and the temperature is maintained for 2 to 4 hours. After that, 161.4 g of hydroxyethyl methacrylate (2-HEMA) is slowly added dropwise, the addition time is 40 to 60 minutes, the temperature is controlled below 60°C during the addition, the addition is completed at 45°C to 60°C and the temperature is maintained for 2 to 4 hours. When the NCO value is lower than 0.5%, 227 g of methyl methacrylate is added for dilution to obtain the polyurethane acrylic resin of Synthesis Example 2, which has a viscosity of 320 cps.
[0071] Synthesis Example 3: 330 g of polymethylene phenyl isocyanate, 0.308 g of 2,5-dihydroxytoluene and 0.179 g of catalyst (DBTDL) are dispersed in 169 g of methyl methacrylate, mixed evenly in a reactor and heated to 45°C to 60°C for standby use. Next, 61.4 g of polypropylene glycol (PPG400) is slowly added dropwise to the above reactor, the addition time is 40 to 60 minutes, the temperature is controlled below 60°C during the addition, the addition is completed at 45°C to 60°C and the temperature is maintained for 2 to 4 hours. After that, 293.6 g of hydroxyethyl methacrylate (2-HEMA) is slowly added dropwise, the addition time is 40 to 60 minutes, the temperature is controlled below 60°C during the addition, the addition is completed at 45°C to 60°C and the temperature is maintained for 2 to 4 hours. When the NCO value is lower than 0.5%, 169 g of styrene is added for dilution to obtain the polyurethane acrylic resin of Synthesis Example 3, which has a viscosity of 300 cps.
[0072] Synthesis Example 4: 270 g of a mixture of 2,4-diphenylmethane diisocyanate and 4,4'-diphenylmethane diisocyanate, 0.287 g of 2,5-dihydroxytoluene and 0.143 g of a catalyst (DBTDL) are dispersed in 167 g of methyl methacrylate, mixed evenly in a reactor and heated to 45°C to 60°C for standby use. Next, 143.6 g of polypropylene glycol (PPG400) is slowly added dropwise to the reactor for 40 to 60 minutes, the temperature is controlled below 60°C during the addition, and the temperature is maintained at 45°C to 60°C for 2 to 4 hours after the addition is completed. After that, 206.7 g of hydroxypropyl methacrylate (2-HPMA) is slowly added dropwise for 40 to 60 minutes, the temperature is controlled below 60°C during the addition, and the temperature is maintained at 45°C to 60°C for 2 to 4 hours after the addition is completed. When the NCO value is lower than 0.5%, 207 g of methyl methacrylate is added for dilution to obtain the polyurethane acrylic resin of Synthesis Example 4, which has a viscosity of 150 cps.
[0073] Synthesis Example 5: 150 g of polymethylene phenyl isocyanate, 0.309 g of 2,5-dihydroxytoluene and 0.181 g of catalyst (DBTDL) are dispersed in 412 g of methyl methacrylate, mixed evenly in a reactor and heated to 45°C to 60°C for standby use. Next, 372.0 g of polypropylene glycol (PPG2000) is slowly added dropwise to the reactor for 40 to 60 minutes, the temperature is controlled below 60°C during the addition, and the temperature is maintained at 45°C to 60°C for 2 to 4 hours after the addition is completed. After that, 96.8 g of hydroxyethyl methacrylate (2-HEMA) is slowly added dropwise for 40 to 60 minutes, the temperature is controlled below 60°C during the addition, and the temperature is maintained at 45°C to 60°C for 2 to 4 hours after the addition is completed. When the NCO value is lower than 0.5%, it is the polyurethane acrylic resin of Synthesis Example 5, and its viscosity is 400 cps.
[0074] <Preparation of polyurethane acrylic resin material>
[0075] The polyurethane acrylic resin material can be a polyurethane acrylic resin cured product and a composite material containing a polyurethane acrylic resin cured product. Specifically, the polyurethane acrylic resins of Synthesis Examples 1 to 5 are added with cobalt isooctanoate (0.1% to 0.2%) and methyl ethyl ketone peroxide (1% to 2%) for room temperature curing for 24 hours, and then baked at 105°C for 2 hours to obtain the polyurethane acrylic resin cured products of Synthesis Examples 6 to 10, respectively. In addition, according to different process operation requirements, the curing system of the polyurethane acrylic resin can be adjusted to an appropriate gelling time for room temperature fiber impregnation molding, and then 105°C and baked for 2 hours to obtain a cured composite material containing fibers.
[0076] <Example / Comparative Example>
[0077] Example 1: 5 g of the polyurethane acrylic resin cured product of Synthesis Example 6 and 2-aminoethanol were placed in a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5, and the temperature was maintained at 135° C. for 10 hours, and a clear solution was obtained, indicating that it can be smoothly degraded.
[0078] Example 2: 5 g of the polyurethane acrylic resin cured product of Synthesis Example 6 and 2-aminoethoxyethanol were placed in a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5, and the temperature was maintained at 135° C. for 24 hours, and a clear solution was obtained, indicating that it can be smoothly degraded.
[0079] Comparative Example 1: 5 grams of the polyurethane acrylic resin solid of Synthesis Example 6 and ethylene glycol were placed in a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5, and kept at 135°C for 24 hours. It showed a complete and undissolved solid, indicating poor degradation efficiency.
[0080] Comparative Example 2: 5 g of the polyurethane acrylic resin solid of Synthesis Example 6 and triethylenetetramine were placed in a round-bottom bottle equipped with a snake-shaped condenser in a weight ratio of 1:5, and the temperature was maintained at 135°C for 24 hours. There was still complete undissolved solid, indicating that the degradation efficiency was poor.
[0081] The resin type, cured product type, degradation liquid type, degradation time (hours) and degradation status of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown in Table 3 below.
[0082]
[0083]
[0084] From the results in Table 3 above, it can be seen that the reactive NH 2 The degradation solution of groups and OH groups can indeed degrade the polyurethane acrylic resin to obtain a clear solution.
[0085] Example 3: 5 g of the polyurethane acrylic resin cured product of Synthesis Example 7 and 2-aminoethanol were placed in a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5, and the temperature was maintained at 135° C. for 10 hours, and a clear solution was obtained, indicating that it can be smoothly degraded.
[0086] Example 4: 5 g of the polyurethane acrylic resin cured product of Synthesis Example 8 and 2-aminoethanol were placed in a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5, and the temperature was maintained at 135° C. for 10 hours, and a clear solution was obtained, indicating that it can be smoothly degraded.
[0087] Example 5: 5 g of the polyurethane acrylic resin cured product of Synthesis Example 9 and 2-aminoethanol were placed in a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5, and the temperature was maintained at 135° C. for 10 hours, and a clear solution was obtained, indicating that it can be smoothly degraded.
[0088] Example 6: 5 g of the polyurethane acrylic resin cured product of Synthesis Example 10 and 2-aminoethanol were placed in a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5, and the temperature was maintained at 135°C for 10 hours to obtain a powdery precipitate solution, indicating that it can be smoothly degraded.
[0089] The resin types, cured product types, degradation time (hours) and degradation states of Examples 3 to 6 are shown in Table 4 below.
[0090]
[0091] Example 7: The glass fiber prepared in Synthesis Example 1 is vacuum infused, and its weight fiber content is controlled to be 68% to 75%. After complete solidification, it is cut into appropriate sizes and loaded into a round-bottom bottle equipped with a snake-shaped condenser at a weight ratio of 1:5 with 2-aminoethanol, and the temperature is maintained at 150°C for 2 hours to obtain a solution for separating the fiber and the polyurethane acrylic resin. The fiber is then washed with ethanol / water and can be successfully recovered.
[0092] Example 8: The carbon fibers prepared in Synthesis Example 1 are vacuum infused, and the weight fiber content is controlled to be 50% to 55%. After complete curing, they are cut into appropriate sizes and loaded into a round-bottom bottle equipped with a serpentine condenser with 2-aminoethanol at a weight ratio of 1:5, and the temperature is maintained at 150°C for 2 hours to obtain a solution for separating the fibers from the polyurethane acrylic resin. The fibers are then washed with ethanol / water and can be successfully recovered.
[0093] Example 9: The aromatic polyamide fibers prepared in Synthesis Example 1 were vacuum infused, and their weight fiber content was controlled to be 50% to 55%. After complete solidification, they were cut into appropriate sizes and loaded into a round-bottomed bottle equipped with a serpentine condenser with 2-aminoethanol at a weight ratio of 1:5. The temperature was maintained at 150°C for 2 hours to obtain a solution for separating the fibers from the polyurethane acrylic resin. The fibers were then washed with ethanol / water and successfully recovered.
[0094] Example 10: The glass fibers of Synthesis Example 3 were hand-laid, and the weight fiber content was controlled to be 30% to 50%. After complete curing, they were cut into appropriate sizes and loaded into a round-bottom bottle equipped with a snake-shaped condenser tube with 2-aminoethanol at a weight ratio of 1:5, and the temperature was maintained at 150°C for 2.5 hours to obtain a solution for separating the fibers and the polyurethane acrylic resin. The fibers were then washed with ethanol / water and the fibers could be successfully recovered.
[0095] The resin type, fiber type, degradation time (hours) and degradation status of Examples 7 to 10 are shown in Table 5 below.
[0096]
[0097] From the results in Table 5 above, it can be seen that the composite material containing polyurethane acrylic resin and fiber is 2 After the degradation liquid of the group and OH group is degraded, the polyurethane acrylic resin can be decomposed and removed to separate the resin from the fiber and leave the fiber without plastic attachment, which can achieve the purpose of recycling the fiber for reuse.
[0098] In summary, the present invention is based on the reactive NH or NH 2The degradation liquid of the groups and OH groups can be heated to degrade the polyurethane acrylic resin material to achieve a high-efficiency depolymerization effect, and the degradation liquid after degradation can be recycled and reused to achieve the purpose of waste reduction.
[0099] Although the present invention has been disclosed in the above embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the claims.
Claims
1. A method for degrading a polyurethane acrylic resin material, characterized in that: Include: providing a polyurethane acrylic resin material, wherein the polyurethane acrylic resin material has a carbon-carbon double bond; and Performing a degradation step, which is to degrade the polyurethane acrylic resin material into degradation products using a degradation compound; Wherein, the degradation products include alcohols or amines.
2. The method for degrading polyurethane acrylic resin material according to claim 1, characterized in that: The degradation products include polyols.
3. The method for degrading polyurethane acrylic resin material according to claim 1, characterized in that: The polyurethane acrylic resin material comprises polyurethane acrylic resin and fibers.
4. The method for degrading polyurethane acrylic resin material according to claim 1, characterized in that: The degradation compound has a structure as shown in formula (i): Wherein, X is an alkyl group or an oxyalkyl group, m is 1 or 2 and m+n=3.
5. The method for degrading polyurethane acrylic resin material according to claim 1, characterized in that: The degradation products include aromatic amines.
6. The method for degrading polyurethane acrylic resin material according to claim 1, characterized in that: The degradation compound comprises a reactive NH group, a reactive NH2 group or a reactive OH group.
7. The method for degrading polyurethane acrylic resin material according to claim 1, characterized in that: The polyurethane acrylic resin material is obtained by curing polyurethane acrylic resin, wherein the polyurethane acrylic resin contains polyurethane acrylic resin oligomers, and the weight proportion of the polyurethane acrylic resin oligomers is more than 40% of the total weight of the polyurethane acrylic resin.
8. The method for degrading polyurethane acrylic resin material according to claim 7, characterized in that: The polyurethane acrylic resin oligomer has a structure as shown in formula (I): Wherein, A is polyethoxy, polypropoxy or polytetrahydrofuranyl.
9. A degradable polyurethane acrylic resin material, characterized in that: Include: Polyurethane acrylic resin having carbon-carbon double bonds; and fiber; Wherein, the fiber is glass fiber, carbon fiber, polyamide fiber or a mixture thereof.
10. A degradable polyurethane acrylic resin material that can be used as a surface coating, characterized in that: Include: Polyurethane acrylic resin having carbon-carbon double bonds; and Titanium dioxide, silicon dioxide, calcium carbonate, aluminum oxide, aluminum hydroxide, silicon carbide or a combination thereof.